Green sustainability assessment and efficiency improvement study of international oil and gas companies: Based on data envelopment analysis - Zuoqian Wang; Zhe Fan (Heliyon)
In the context of carbon neutrality, the oil and gas industry is facing increasingly stringent environmental regulatory pressures, posing severe challenges to enterprise sustainability development. This study proposes a new comprehensive calculation model to investigate the effects of low-carbon transformation and development of petrochemical enterprises in recent years. It can effectively quantify the relative efficiency of different samples in the same time interval and the efficiency change of a single sample in the time series. It can also perform individual assessments of operational or environmental levels for a more comprehensive analysis perspective. Furthermore, the study included the enterprises' carbon footprint of scope 3 in the calculation framework for the first time makes the study results more realistic and forward-looking in reflecting the enterprises’ green management level. The model has been applied to 32 international oil and gas production and refining enterprises. The differences where the companies are located, the types of companies, and the value chain show different efficiency characteristics.In sum, the study results show that the petrochemical industry is actively implementing a low-carbon development strategy and will continue to do so. In the context of the expansion of petrochemical products, the refining field should receive more attention.